Cost-effectiveness of cadonilimab plus chemotherapy vs chemotherapy alone for advanced gastric cancer: evidence to inform drug pricing in the U.S. and China - Lang, Wenwang; Mei, Liuyong; Xiao, Qiang; Zhou, Zujin; Jiang, Huiqing; Zhao, Xianling (Frontiers in Immunology, 2025)
BackgroundCadonilimab, a bispecific antibody targeting programmed cell death protein 1 (PD-1) and cytotoxic T-lymphocyte-associated protein 4 (CTLA-4), was the first agent of its class to demonstrate promising therapeutic efficacy in combination with chemotherapy for patients diagnosed with advanced gastric or gastroesophageal junction adenocarcinoma (GC/GEJC). This economic evaluation aimed to determine whether cadonilimab plus chemotherapy offers cost-effective benefits compared to chemotherapy alone from both the U.S. and Chinese healthcare payer perspectives. In addition, we estimated the pricing thresholds at which cadonilimab would be considered economically viable as a first-line treatment.MethodsWe constructed a Markov model comprising three health states, progression-free survival (PFS), progressive disease (PD), and death, spanning a 10-year time horizon. The clinical efficacy data were sourced from the randomized phase 3 COMPASSION-15 trial. The cost and utility parameters were derived from existing literature. The model calculates total costs, quality-adjusted life-years (QALYs), and incremental cost-effectiveness ratios (ICERs). Subgroup, scenario, and sensitivity analyses were performed, and price simulations explored cost-effective thresholds at defined willingness-to-pay (WTP) levels.ResultsIn the base-case analysis, the cadonilimab plus chemotherapy provided an incremental gain of 0.33 QALYs at an additional cost of $16,797.61, resulting in an ICER of $50,582.10 per QALY, above the WTP threshold of China of $40,354.27 per QALY. In the U.S. setting, although the combination therapy achieved a slightly higher incremental QALY gain of 0.35 QALYs, the substantial additional cost of $101,275.06 resulted in an unfavorable ICER of $290,498.45 per QALY, exceeding the U.S. WTP threshold of $150,000.00. Among Chinese patients with a PD-L1 combined positive score (CPS) ≥5, the ICER was lower at $37,499.27/QALY, rendering the therapy cost-effective. Simulations identified cadonilimab pricing below $209.54/125 mg (China) and $826.46/125 mg (the U.S.) as necessary for cost-effectiveness.ConclusionCadonilimab combined with chemotherapy may be cost-effective in Chinese patients with elevated PD-L1 expression. However, its broader use in other patient subgroups or countries requires significant price reductions. These findings provide important guidance for future reimbursements and pricing decisions.